Incidence and Outcome of Peri-interventional Vasospasm During Endovascular or Microsurgical Treatment of Unruptured Intracranial Aneurysms. Issue 3 (2nd March 2023) - Grüter, Basil E.; Wanderer, Stefan; Andereggen, Lukas; Tortora, Angelo; Gruber, Philipp; Anon, Javier; Diepers, Michael; Schubert, Gerrit; Remonda, Luca; Marbacher, Serge
Abstract : BACKGROUND: Peri-interventional vasospasm (PIVS) is associated with high risk of delayed cerebral vasospasm (DCVS), delayed cerebral ischemia, and poor outcome after aneurysmal subarachnoid hemorrhage. However, the incidence rate associated with treatment of unruptured intracranial aneurysm (UIA) remains unclear. OBJECTIVE: To define the incidence and clinical significance of PIVS in UIA repair based on intraoperative/peri-interventional digital subtraction angiography. METHODS: A consecutive series of 205 patients who underwent UIA treatment by means of microsurgical clipping (n = 109) or endovascular coil embolization (n = 96) was assessed for the occurrence of PIVS. In all cases, PIVS was detected, measured, and classified using intraoperative/peri-interventional digital subtraction angiography. Severity of PIVS, association of PIVS with the development of DCVS, and neurological outcome were analyzed. RESULTS: Intraoperative PIVS was present in n = 14/109 (13%) patients with microsurgical clipping. Of these, caliber irregularities were mild (n = 10), moderate (n = 3), and severe (n = 1). In endovascularly treated patients, 6/96 (6%) developed PIVS, which were either mild (n = 3) or moderate (n = 3). Management in all cases included immediate intensive blood pressure management and application of topical papaverine or intra-arterial nimodipine immediately on detection of PIVS. No patient developed DCVS or lasting neurological deficits attributable to PIVS. CONCLUSION: This series revealed a relatively high overall incidence of PIVS (10%). However, no association of PIVS with the development of DCVS or poor outcome was found. In contrast to ruptured intracranial aneurysms, PIVS in unruptured intracranial aneurysms—if immediately and adequately addressed—seems to be benign and without sequelae for patient's functional outcome.